2022
DOI: 10.3390/ijms23179914
|View full text |Cite
|
Sign up to set email alerts
|

Viral Infection and Airway Epithelial Immunity in Asthma

Abstract: Viral respiratory tract infections are associated with asthma development and exacerbation in children and adults. In the course of immune responses to viruses, airway epithelial cells are the initial platform of innate immunity against viral invasion. Patients with severe asthma are more vulnerable than those with mild to moderate asthma to viral infections. Furthermore, in most cases, asthmatic patients tend to produce lower levels of antiviral cytokines than healthy subjects, such as interferons produced fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 181 publications
0
13
0
Order By: Relevance
“…Viral infection of the airways also has profound effects on epithelial barrier function [ 42 ]. Facilitated by a disrupted barrier, viral infection activates epithelial cells, triggering innate immune and T2 inflammatory responses, and amplifying the overall inflammation commonly present in asthma [ 42 44 ].…”
Section: Airway Epithelial Barrier Disruptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Viral infection of the airways also has profound effects on epithelial barrier function [ 42 ]. Facilitated by a disrupted barrier, viral infection activates epithelial cells, triggering innate immune and T2 inflammatory responses, and amplifying the overall inflammation commonly present in asthma [ 42 44 ].…”
Section: Airway Epithelial Barrier Disruptionmentioning
confidence: 99%
“…Viral infection of the airways also has profound effects on epithelial barrier function [ 42 ]. Facilitated by a disrupted barrier, viral infection activates epithelial cells, triggering innate immune and T2 inflammatory responses, and amplifying the overall inflammation commonly present in asthma [ 42 44 ]. However, the immune response to viral infection appears to be deficient and delayed in people with asthma, with reduced production of type I IFN and other cytokines in epithelial and dendritic cells leading to greater damage to the airway epithelium [ 45 47 ].…”
Section: Airway Epithelial Barrier Disruptionmentioning
confidence: 99%
“…Among respiratory viruses, rhinovirus is the most important and common virus that exacerbates asthma. 50 Asthma patients may have deteriorating asthma symptoms as a result of the functional interplay between viral pathology and asthma pathology. 51 Recurrent asthma inflammation may hinder the body’s ability to mount an efficient antiviral defense, worsening the virus’s already-present airway destruction.…”
Section: The Possible Mechanism Related To Damentioning
confidence: 99%
“…Studies have shown that opening the epithelial barrier induces inflammatory responses and increased epithelial permeability, creating a vicious cycle that potentiates dysregulated subepithelial immune responses and more exposure to allergens and irritants. 70 132 Cell-cell adhesion complexes (TJ, AJ, desmosome) are the key regulators of paracellular permeability. 133 TJs defects and increased epithelial permeability are the main characteristics of chronic airway disease and leaky gut syndrome.…”
Section: Epithelial Barrier Dysfunction In Allergic Diseasesmentioning
confidence: 99%